Sosialisasi Perwasitan Terbaru Bola Basket sebagai Upaya Peningkatan Pemahaman Aturan Permainan bagi Mahasiswa FIKK UNM - Syamsuddin, Muh Syachrul; Sutriawan, Agus; Syafruddin, Muhammad Akbar; Fadlih, Andi Muhammad; Raswadi, Mohammad Dika (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to improve students' understanding of the latest basketball rules through a socialization of refereeing in accordance with official FIBA regulations. This activity was held for three days at the Faculty of Sport and Health Sciences (FIKK) of Makassar State University and was attended by 120 students from various study programs. The implementation method included theoretical material delivery, interactive discussions, situational case studies, and on-field refereeing simulation practice. The main material provided included updates to game rules, refereeing mechanisms, the use of referee signals, and the application of decisions in match situations. The results of the activity showed a significant increase in participants' understanding of refereeing rules and techniques, as evidenced by their enthusiasm during the discussion session, their ability to answer evaluation questions, and their improved skills in refereeing simulation practice. This activity is expected to provide initial provisions for FIKK UNM students to apply their knowledge of basketball refereeing correctly in academic activities, internal competitions, and community service within the school environment and sports communities.